1980
DOI: 10.1159/000119909
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Evaluation of Continuous Intracranial Pressure Monitoring in Pediatric Hydrocephalus

Abstract: An evaluation of continuous intracranial pressure (ICP) monitoring in 42 hydrocephalic infants and children helps to establish the role of this method in comparison with other clinical techniques for estimating the occurrence of progressive hydrocephalus. Transducer monitoring via ventricular catheters in term and premature infants revealed average ICP in the 5–12 mm Hg range. The higher values were recorded from patients with noncommunicating hydrocephalus but did not correlate with the extent of ventriculome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…16 The presence of B-waves is indicative of reduced intracranial compliance, and they appear mainly during the rapid eye movement (REM) sleep when there is an increase in cerebral blood flow (CBF) and brain metabolism. [18][19][20][21] The alteration of cerebral autoregulation or reactivity due to reduced intracranial compliance could be pathological in such a scenario.…”
Section: Introductionmentioning
confidence: 99%
“…16 The presence of B-waves is indicative of reduced intracranial compliance, and they appear mainly during the rapid eye movement (REM) sleep when there is an increase in cerebral blood flow (CBF) and brain metabolism. [18][19][20][21] The alteration of cerebral autoregulation or reactivity due to reduced intracranial compliance could be pathological in such a scenario.…”
Section: Introductionmentioning
confidence: 99%
“…23 Following an evidentiary analysis and a review of the 98 full-text articles, 68 publications were accepted for inclusion in the evidentiary table and 30 publications were excluded. 2,7,[12][13][14]21,22,27,30,33,35,38,48,[50][51][52][53]55,57,58,[62][63][64][66][67][68]70,73,75 The evidentiary table was assembled linking recommendations to the strength of the evidence (Levels I-III).…”
Section: Strategymentioning
confidence: 99%
“…It is generally agreed that there is a relation between ICP and the age of children, with ICP values progressively increasing from subatmospheric levels in the neonate to a range of 20-70 mm H 2 O during infancy and ultimately to its adult levels by the age of eight years. [46][47][48] Several studies reported in the literature have shown that a condition comparable with NPH may not be uncommon in childhood. [49][50][51][52][53][54][55][56] From a clinical standpoint, a paediatric form of the triad may be characterised as follows: v Subtle mental deterioration manifested by poor or decreasing scholar performances; v Anomalies of gait manifested either by walking retardation in infants or by repeated falling spells in older children; v Anomalies of micturition with delayed bladder control, whose relation to hydrocephalus is frequently overlooked or ascribed to enuresis.…”
Section: Is Nph Specific To the Adult And Elderly Population?mentioning
confidence: 99%